Pengaruh Jumlah Buah dan Jenis Kemasan Terhadap Sifat-Fisiko-Kimia dan Umur Simpan Buah Paprika Segar (Capsicum annuum var. grossum) - Yudistira, Dewa Putu Jnana Puja; Mahendra, Made Sudiana; Sugiarta, Anak Agung Gede (Nandur, 2023)
The demand for bell pepper is increasing along with the growth of the economy and population. This study aims to investigate the effect of the appropriate quantity of fruit in the packaging and determine the suitable packaging type for preserving the physicochemical properties and shelf life of bell pepper. The research is being conducted from February to March 2023 at the Eco-physiology Laboratory, Faculty of Agriculture, Udayana University The experimental design used is a completely randomized design (CRD) with a factorial pattern consisting of 2 factors. The first factor is the packaging treatment (K), which includes three treatments: K 0 = Control (without packaging), K 1 = Polypropylene (PP) packaging, and K 2 = Polyethylene (PE) packaging. The second factor is the quantity of fruit (T), consisting of two treatments: T 1 = 2 fruits in one package and T 2 = 3 fruits in one package. Each treatment is replicated 4 times, resulting in a total of 24 experimental units. The research findings indicate an interaction between the packaging type and the quantity of fruit for the variable of shelf life. The quantity of fruit has a highly significant effect on weight loss on the 4th and 8th day and a significant effect on the shelf life , whereas the packaging type has a highly significant effect on the shelf life, the total soluble solids (TSS) content on the 8th day, and a significant effect on weight loss on the 4th and 8th day. Furthermore, the highest increase in vitamin C is observed in K 0 T 1 , which records a 198.47% increase.